Understanding the opportunities and challenges of reverse logistics : A study of the Finnish construction plastics manufacturing industry - Marttila, Tuomas (My University, 2023)
The purpose of this study is to investigate how Finnish construction plastics manufacturing companies engage in reverse logistics and how various drivers and barriers affect it. Interest in the circular economy is constantly growing, and as a result, reverse logistics as part of the circular economy initiative has become an increasingly important aspect of logistics. More than a fifth of all plastic produced is used for the needs of the construction industry, making construction plastics the second-largest use of plastics after packaging. However, the reuse and recycling of plastics are not yet at the desired level. This study is conducted as a qualitative multiple-case study, that has its theoretical framework built on academic literature on the topic of reverse logistics and its various dimensions. The main research question of the study focuses on how different drivers and barriers affect reverse logistics in Finnish construction plastics manufacturing companies. To support this main research question, two supporting questions have been formulated, which relate to the current reverse logistics practices of the companies and the role of reverse logistics in achieving sustainability goals. The empirical data gathered for the study was collected through semi-structured interviews that were conducted with five different Finnish companies operating in the Finnish construction plastics manufacturing sector. The results of the study indicate that while reverse logistics is to some extent practiced in the case companies, it is not yet highly developed, and companies are facing several challenges regarding its profitability and further implementation. The interview data reveals that although there are various drivers that drive the development of reverse logistics in the construction plastics manufacturing industry, there are also numerous barriers that negatively impact reverse logistics and its implementation. However, the case companies for the most part perceive reverse logistics as an important part of business in the future. Despite this, the development and enhancement of reverse logistics is not the main priority within the companies as of now, even though its significance for sustainable business is quite well understood. This study partially fills a gap in the literature on reverse logistics by providing a more detailed understanding of why and how various drivers and barriers affect reverse logistics, as previous research has mainly focused on merely identifying different drivers and barriers across industries. Additionally, the study offers up-to-date information on reverse logistics within the relatively underexplored plastics manufacturing industry. The study contributes to laying the groundwork for further research on overcoming the barriers that hinder reverse logistics in the plastics manufacturing sector.

Tämän tutkimuksen tarkoituksena on selvittää, miten suomalaiset rakentamisen muovien valmistukseen keskittyvät yritykset harjoittavat paluulogistiikkaa ja miten erilaiset ajurit ja esteet vaikuttavat siihen. Kiinnostus kiertotalouteen on kasvussa ja sitä kautta paluulogistiikasta osana kiertotaloutta on tullut entistä tärkeämpi logistiikan osa-alue. Yli viidesosa kaikesta tuotetusta muovista käytetään rakennusteollisuuden tarpeisiin, tehden rakentamisen muoveista toiseksi suurimman muovien käyttötarkoituksen heti pakkausmuovien jälkeen. Muovien uusiokäyttö ja kierrätys ei kuitenkaan vielä ole sillä tasolla, jolla sen toivottaisiin olevan. Tämä tutkimus on toteutettu laadullisena monitapaustutkimuksena, jonka viitekehys on rakennettu paluulogistiikkaan ja sen ulottuvuuksiin liittyvän aiemman akateemisen kirjallisuuden pohjalta. Tutkimuksen päätutkimuskysymys keskittyy siihen, kuinka eri ajurit ja esteet vaikuttavat paluulogistiikkaan suomalaisissa rakennusmuoveja valmistavissa yrityksissä. Tätä päätutkimuskysymystä tukemaan on asetettu kaksi apukysymystä, jotka liittyvät yritysten nykyisiin paluulogistiikkakäytäntöihin sekä paluulogistiikan rooliin kestävyystavoitteiden saavuttamisessa. Tutkimuksen empiirinen aineisto on kerätty puolistrukturoitujen haastatteluiden avulla viidestä eri suomalaisesta rakennusmuoveja valmistavasta yrityksestä. Tutkimuksen tulokset osoittavat, että vaikka paluulogistiikkaa pääsääntöisesti harjoitetaan suomalaisissa rakennusmuoveja valmistavissa yrityksissä joissain määrin, ei se pääosin ole vielä kovin kehittyneellä tasolla ja yrityksillä on sen kannattavuuden suhteen monia haasteita ratkaistavina. Haastatteluaineistosta käy ilmi, että vaikka paluulogistiikan kehittämiselle on muoviteollisuudessa useita eri ajureita, on olemassa myös suuri määrä esteitä, joilla on negatiivinen vaikutus paluulogistiikkaan ja sen kehittämiseen. Paluulogistiikka koetaan kuitenkin haastatelluissa yrityksissä pääosin tärkeänä osana liiketoimintaa tulevaisuudessa. Tällä hetkellä sen kehittäminen ja tehostaminen ei kuitenkaan ole yrityksissä ensisijaista siitä huolimatta, että sen merkitys kestävän liiketoiminnan kannalta on varsin hyvin ymmärretty. Tutkimus täyttää osaltaan aukkoa paluulogistiikkaan liittyvässä kirjallisuudessa, sillä se tarjoaa yksityiskohtaisemman näkemyksen sille, miksi ja miten erilaiset ajurit ja esteet vaikuttavat paluulogistiikkaan aikaisemman tutkimuksen keskittyessä pääosin vain tunnistamaan, mitä eri ajureita ja esteitä eri toimialoilla on olemassa. Lisäksi tutkimus tarjoaa ajankohtaista tietoa paluulogistiikasta muoviteollisuudesta, jota on aikaisemmassa tutkimuksessa käsitelty vain vähän. Tutkimus luo osaltaan perustan jatkotutkimuksille koskien sitä, miten erilaiset paluulogistiikan tiellä seisovat esteet voidaan ylittää muoviteollisuudessa.
Keywords: reverse logistics, construction plastics, plastics manufacturing industry, closed-loop supply chain, circular economy, sustainability, paluulogistiikka, rakennusmuovit, muoviteollisuus, suljettu kierto, kiertotalous, kestävyys